Two new species of the genus Arboridia Zachvatkin (Hemiptera: Auchenorrhyncha: Cicadellidae: Typhlocybinae) from Korea - Oh, Sumin; Choe, Kwang-Ryul; Jung, Sunghoon (Zootaxa, 2015)
Two new species of the genus Arboridia Zachvatkin, A. koreana sp. nov., A. septempunctata sp. nov., are described from Korea. Photographs of dorsal habitus, illustrations of male genitalia, abdomens and forewings, and biological information such as host plants and distributional records and a key to the Korean Arboridia species are provided.